Efektivitas Akun Tiktok @CNNIndonesia dalam Memenuhi Kebutuhan Informasi Generasi Z Mahasiswa Komunikasi Penyiaran Islam Stambuk 2021 UIN Sumatera Utara - Al Syahdafi; Erwan Efendi (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
TikTok as a short video-based social media platform has become one of the dominant news sources among students. This study aims to analyze the effectiveness of the TikTok account @cnnindonesia as a news media in meeting the information needs of generation Z, especially students of the Faculty of Da'wah and Communication, Islamic Broadcasting Communication Study Program, class of 2021, UIN North Sumatra. This study uses a qualitative descriptive method with data collection techniques through indepth interviews, observations, and documentation studies. Interviews were conducted with 10 students who actively use TikTok as a source of news information. The results of the study show that the TikTok account @cnnindonesia is effective in presenting concise, interesting, and easily accessible news. Presenting news with a short duration, attractive visuals, and active interaction with users are the main factors that make this account popular with students. Most respondents trust the credibility of the @cnnindonesia account because it is part of a major news media with a good reputation. However, some respondents still verify information through other sources to ensure the accuracy of the news received. The results of the study also show that TikTok is not just an entertainment platform, but also has an important role in disseminating educational and useful information for students. This study concludes that the TikTok account @cnnindonesia is effective in meeting the information needs of generation Z students at UIN North Sumatra. However, it is important for students to continue to apply digital literacy in order to sort out valid information and avoid hoax news.